Potential energy surface of H2O on Al{111} and Rh{111} from theoretical methods - Ranea, Víctor Alejandro (2012)
The potential energy surfaces of molecular water on the Al{111} and on the Rh{111} metal surfaces have been investigated using density functional theory. Similarlandscapes were found on both surfaces. In the only minimum found, the watermolecule is monocoordinated to the surface via the oxygen atom (top configuration)with its plane nearly parallel to the surface. The maxima are around the bridgeand hollow configurations and no local minima or local maxima were found. Alongthe investigated minimum energy pathways, no strong preferential orientation ofthe water dipole was found, as long as the molecular plane is nearly parallel to thesurface.